PENGEMBANGAN SKENARIO PEMBELAJARAN BERBASIS COOPERATIVE LEARNING DAN DISCOVERY LEARNING DALAM MENGANALISIS NOVEL - Ocha Holida; Munaris Munaris; Ali Mustofa (FKIP Universitas Lampung, 2020)
The problem in this research is how the development of a learning scenario based on cooperative learning and discovery learning in novel text for SMA class XII. The purpose of this study is to describe the development of a learning scenario based on cooperative learning and discovery learning in novel text for SMA class XII. This research uses research and development (rnd) method. The result of this study is the creation of a learning scenario product in novel text for SMA class XII that has been validated. Validation is conducted by expert lecturers to test the feasibility of the product. The result of the validation is from material expertson the learning aspectobtainedan average percentage of 93.18%, and the content aspect obtained an average percentage of 93.18% with very decent criteria.Masalah dalam penelitian ini ialah bagaimana pengembangan skenario pembelajaran berbasis cooperative learning dan discovery learning teks novel kelas XII SMA. Tujuan penelitian ini untuk mendeskripsikan pengembangan skenario pembelajaran berbasis cooperative learning dan discovery learning teks novel kelas XII SMA. Penelitian ini menggunakan metode research and development (rnd). Hasil penelitian ini ialah terciptanya produk skenario pada pembelajaran novel di SMA Kelas XII kelas yang sudah divalidasi.Validasi dilakukan oleh dosen ahli untuk menguji kelayakan produk. Hasil validasi dari ahli materi pada aspek pembelajaran diperoleh rata-rata persentase 93,18%, dan pada aspek isi diperoleh rata-rata persentase 93,18% dengan kriteria sangat layak. Keywords: scenario development, cooperative learning, discovery learning, novel.